Olink proteomics profiling platform reveals non-invasive inflammatory related protein biomarkers in autism spectrum disorder - Bao, Xiao-Hong; Chen, Bao-Fu; Liu, Jun; Tan, Yu-Hua; Chen, Shu; Zhang, Fan; Lu, Hong-Sheng; Li, Ji-Cheng (Frontiers in Molecular Neuroscience, 2023)
Background: Owing to the lack of valid biomarkers, the diagnosis of autism spectrum disorder (ASD) diagnosis relies solely on the behavioral phenotypes of children. Several researchers have suggested an association between ASD and inflammation; however, the complex relationship between the two is unelucidated to date. Therefore, the current study aims to comprehensively identify novel circulating ASD inflammatory biomarkers. Methods: Olink proteomics was applied to compare the plasma inflammation-related protein changes in a group of the healthy children (HC, n=33) and another with ASD(n=31). The areas under the receiver operating characteristic curves (AUCs) of the differentially expressed proteins (DEPs) were calculated. The functional analysis of the DEPs was performed using Gene Ontology and Kyoto Encyclopedia Genes and Genomes. Pearson correlation tests were used employed to analyze the correlation between the DEPs and clinical features. Results: A total of 13 DEPs were significantly up-regulated in the ASD group compared with the HC group. The four proteins, namely, STAMBP, ST1A1, SIRT2, and MMP-10 demonstrated good diagnostic accuracy with the corresponding AUCs (95% confidence interval, CI) of 0.7218 (0.5946–0.8489), 0.7107 (0.5827–0.8387), 0.7016 (0.5713–0.8319), and 0.7006 (0.568–0.8332). Each panel of STAMBP and any other differential protein demonstrated a better classification performance [AUC values from 0.7147 (0.5858–0.8436, STAMBP/AXIN1) to 0.7681 (0.6496–0.8867, STAMBP/MMP-10)]. These DEP profiles were enriched in immune and inflammatory response pathways, including TNF and NOD-like receptor signaling pathways. The interaction between STAMBP and SIRT2 (R=0.97, p=8.52× 10-39) was found to be the most significant. In addition, several DEPs related to clinical features in patients with ASD, particularly AXIN1 (R=0.36, p =0.006), SIRT2 (R=0.34, p =0.010) and STAMBP (R=0.34, p =0.010), were positively correlated with age and parity, indicating that older age and higher parity may be the inflammation-related clinical factors in ASD. Conclusion: Inflammation plays a crucial role in ASD, and the up-regulated inflammatory proteins may serve as potential early diagnostic biomarkers for ASD.